Reclaiming indigenous voices: linguistic landscape of minority languages in urban public spaces in Indonesia - Winie Setia Prilapnita Hapsari; Alif Via Sufianti (Indonesian Journal of Language and Communication Studies, 2026)
Background: The visibility of minority languages in Indonesia’s urban public spaces reflects complex dynamics of cultural identity, political recognition, and linguistic equity. Objective: This study aims to examine the distribution, symbolic meanings, and power relations embedded in the linguistic landscape of selected Indonesian cities. Method: Employing a qualitative design that integrates Linguistic Landscape Analysis, semiotics, and Critical Discourse Analysis, data were collected through photographic documentation, field observations, municipal policy reviews, and stakeholder interviews. Results: The findings show that Makassar, Bandung, and Kupang exhibit high-visibility and institutionally supported minority language signage, integrating cultural identity with commercial and governance domains. Jayapura’s linguistic presence is dominated by political assertion and artistic expression, while Jakarta and Surabaya show lower visibility, with indigenous languages often confined to informal or peripheral spaces. These patterns indicate that ethnolinguistic vitality, governance frameworks, and socio-political histories strongly influence language placement, symbolic resonance, and public legitimacy. Implication: The study implies that sustainable indigenous language visibility requires not only spatial representation but also systemic policy support and community engagement. Novelty: This study demonstrates how governance structures and ethnolinguistic vitality jointly shape the visibility and symbolic power of minority languages in urban Indonesia through an integrated linguistic landscape, semiotic, and critical discourse perspective.